Delayed Management of a Button Battery Foreign Body in the Esophagus: A Case Report - Mizwar, Mizwar; Asyari, Ade (Jurnal Ilmu Kesehatan Indonesia, 2025)
Introduction: A Foreign body ingestion and ofreign body aspiration commonly affect children between 6 months and 6 years. Items that are commonly swallowed by children are small and shiny object, such button batteries and magnets that have increased rapidly over the last decade. Botton battery ingestion an established surgical emergency, requiring immediate removal. Delay in diagnosis can lead possible complication such as inflammation, necrosis of esophageal mucosa and esophageal perforation. Rigid esophagoscopy is mainstay procedure of management foreign body in esophagus. Case Report: A case of foreign body battery in esophagus was reported in a 4 year old girl with chief complain felt something stuck at the throat since 3 days before admission and patient performed thoracal x-ray. Esophagoscopy was performed to remove battery foreign body in esophagus. At the time of evaluation, necrosis and excoriation was found in the esophagus as high as 18 cm from the incisivus. Conclusions: Delay in diagnosis and management of foreign battery in the esophagus could lead in to severe clinical manifestations and could cause the complication. Esophagoscopy remains the mainstay management of foreign body in esophagus because of its good visualization.